2018
DOI: 10.18203/2349-2902.isj20180038
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of thyroid swellings in HSK hospital in Karnataka, India

Abstract: Background: A thyroid enlargement whether diffuses or in the form of nodules have to be investigated to rule out neoplasm. FNAC is the first line of investigation. USG and TFT are also used. The cases which are at high risk are considered for surgery. Aims and objectives of the study was the clinical presentation of thyroid swellings, incidence of various thyroid swelling, benign versus malignant lesion and to correlate the clinical diagnosis with that of pathological diagnosis.Methods: A case series study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The most common variety was lymphocytic thyroiditis and colloid goitre followed by papillary carcinoma and medullary carcinoma. This study is corroborated with Halbhavi SN et al (30) who studied 22 operated cases out of 60 patients in which 3.33% were malignant and 33.33% were benign.…”
Section: Discussionsupporting
confidence: 83%
“…The most common variety was lymphocytic thyroiditis and colloid goitre followed by papillary carcinoma and medullary carcinoma. This study is corroborated with Halbhavi SN et al (30) who studied 22 operated cases out of 60 patients in which 3.33% were malignant and 33.33% were benign.…”
Section: Discussionsupporting
confidence: 83%
“…It may present as a nodule (single or multiple), generalised diffuse swelling or with grossly altered gland architecture (as in multinodular goitre) along with normal or deranged serum thyroid profile. 1 Thyroid diseases are common worldwide and in India too there is a significant burden of thyroid disease. It has been estimated that thyroid disease has a reported prevalence of 4% to 7% in the general population on neck palpation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results disagree with what found by Santosh et al, were he revealed in their study that only 10% of cases of malignant and Halbhavi et al, who found also only 10.3% of his cases belonged to malignant group. 8,10 As well as Borsaikia and Patar, who found that follicular carcinoma (4.24%) was more commonly than papillary carcinoma (1.41%). 9 Our results revealed increase serum level of TSH in malignant cases than in benign cases and this was agree with what reported by Tamhane and Gharib in their study that Boelaert et al, and Haymart et al, where they concluded in their studies that increased serum TSH or TSH even in the upper limit of normal is associated with increased risk and advanced stage of malignancy which.…”
Section: Discussionmentioning
confidence: 87%
“…Our study revealed that the age was older in malignant cases and females were commonly affected than males [8][9][10] Neck swelling was the main presenting symptom in our cases which was mainly nodular with little cases of smooth swelling which was in agreement with Santosh et al, Borsaikia and Patar and Halbhavi et al [8][9][10] The histopathologic examination of our cases revealed that the most common benign thyroid swelling was multinodular goiter followed by thyroid adenoma while the most common malignant thyroid swelling was papillary carcinoma followed by follicular carcinoma. Tamhane and Gharib, revealed in their study that the most common malignant carcinoma was the papillary carcinoma (97-99%) and follicular carcinoma constitute about little percentage which agreed with our results.…”
Section: Discussionmentioning
confidence: 99%